Pengaruh Red Flags, Kompetensi Auditor, Dan Pengalaman Kerja Auditor, Terhadap Kemampuan Auditor Dalam Mendeteksi Fraud - Moch Deny Setiawan; Immanuel Calvin Fernaldi; Tri Ratnawati (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
This article aims to find out how red flags, professional skepticism, and work experience influence the auditor's ability to detect fraud. This article will explain how red flags, competency, and auditor work experience influence the auditor's ability to detect fraud. This research method uses the literature study method. Based on the data that has been collected.